Role of FOXO3a Transcription Factor in the Regulation of Liver Oxidative Injury - Hong Jin; Li Zhang; Jun He; Min Wu; Li Jia; Jiabin Guo (MDPI AG, 2022)
Oxidative stress has been identified as a key mechanism in liver damage caused by various chemicals. The transcription factor FOXO3a has emerged as a critical regulator of redox imbalance. Multiple post-translational changes and epigenetic processes closely regulate the activity of FOXO3a, resulting in synergistic or competing impacts on its subcellular localization, stability, protein-protein interactions, DNA binding affinity, and transcriptional programs. Depending on the chemical nature and subcellular context, the oxidative-stress-mediated activation of FOXO3a can induce multiple transcriptional programs that play crucial roles in oxidative injury to the liver by chemicals. Here, we mainly review the role of FOXO3a in coordinating programs of genes that are essential for cellular homeostasis, with an emphasis on exploring the regulatory mechanisms and potential application of FOXO3a as a therapeutic target to prevent and treat liver oxidative injury.